Biology, ecology and dynamics of pennant's swimming crab (Portumnus latipes) in the south of Portugal - Reyes, Claudia Cores (2015)
Dissertação de mestrado, Biologia Marinha, Faculdade de Ciências e Tecnologia, Univesrsidade do Algarve, 2015 The sand crab (Portumnus latipes) is found on exposed sandy beaches of the north-east Atlantic and parts of the Mediterranean, where it burrows in the fine sand in the surf zone. Little is known of the biology and ecology of the species that is caught as by-catch in dredges and is an important prey of several commercial species such as sea bass (Dicentrarchus labrax), gilthead seabream (Sparus aurata) and white seabream (Diplodus sargus). Samples were taken bi-monthly between February and June 2015 in Faro beach, on the coast of the Algarve, southern Portugal. Individuals were collected using manual Ganchorra. Sampling for experimental fieldworks was carried out at low tide using Sardine pilchardus as a bait attached to metal stakes to attract the crabs that were then caught by hand. Female:male sex ratio was 1.56:1 and highest percentage of berried females was recorded between February and April. Fecundity values were 35.334, 45.201 and 26.448 for Stage I, II and III respectively. Number of eggs per gram of sample was constant across all sizes. Minimum and maximum length was 11.10 mm - 25.30 mm for males and 10.54 mm -21.85 mm for females. Estimated Von Bertalanffy growth parameters were ????∞ = 34.83mm; K= 0.52y-1; t0= -0.41 and ???? ∞ = 27,16mm; K= 0.74y-1; t0= -0.39y for females using ELEFAN implemented in the LFDA package. Markrecapture field studies recorded a density of 6 individuals per m2. Minimum distance at which there are no overlapping between traps was 10.6 m, with an area of attraction of 88.099 m2/trap. Portumnus latipes is widely distributed along the Portuguese coast. During an IPMA (Portuguese Institute for the Ocean and Atmosphere) survey, P. latipes was recorded from 3 to 28m depths, with greatest abundance at 3m and highest abundance per tow from the south coast of Portugal. No presente estudo o Caranguejo-de-areia, Portumnus latipes (Pennant, 1777), um crustáceo pertencente ao grupo ...